Unpacking the imaginary in literacies of globality. Issue 4 (3rd July 2020) - Perry, Mia
ABSTRACT: As global mobility and communications proliferate, ever-increasing exchanges and influences occur across cultures, geographies, politics, and positions. This paper addresses the practice of literacy education in this context, and in particular the nature of engagement across difference and the role of the imaginary in literacies of globality. Grounded in a theorisation of difference and the imaginary in spaces of learning and inquiry, the paper proposes a methodological framework for working across difference that acknowledges and engages with the inevitable but enigmatic resource of often conflicting imaginaries in literacy practices.